Peranan Badan Usaha Milik Desa (Bumdesa) Dalam Meningkatkan Pertumbuhan Ekonomi Para Petani di Desa Gudangkahuripan Kecamatan Lembang Kabupaten Bandung Barat - Enang Narlan Soetiman AP (Lembaga Penelitian Universitas Langlangbuana, 2019)
The research method used is a quantitative method. Data collection was done by distributing questionnaires to 389 restaurant visitors. Data analysis techniques using Conjoint Analysis. This study uses qualitative methods, which have natural characteristics as a direct, descriptive data source, the process is more important than the results, analysis in qualitative research tends to be done in inductive analysis and meaning is essential. Data collection in this study are interviews, observation and documentation. The results of the data analysis are in the form of exposure relating to the situation being studied and presented in the form of narrative descriptions. The results of the research in the field show that BUMDesa in Gudangkahuripan Village, Kec. Lembang Kab. West Bandung shows quite encouraging developments, especially in the PAM, Trade, Tourism, Parking, Animal Husbandry and Copy Photo sectors (although management is not fully managed by BUMDesa). But in the agricultural sector it can be said that it has not been touched at all. With the establishment of BUMDesa, the level of economic growth in the community feels better, but unfortunately the economic growth has not been evenly felt by most farmers, especially in terms of minimal capital and insights into traditional gardening techniques.